Greek sanctuaries and temple architecture an introduction - Emerson, Mary (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"An introduction to ancient Greek sanctuary sites and temple architecture, explaining technical terms and aesthetic concepts behind Greek architectural design"